Hysteresis and eddy currents compensation in current transformers. - Locci, N. (IEEE Transactions on power delivery)
In the paper a digital technique for improving the accuracy of instrument current transformers is presented. Since the exciting current can be considered as the main error source, its evaluation can allow the compensation of its detrimental effects to be obtained. The exciting current required by the transformer in every kind of steady state operation can be determined by simply acquiring the secondary current, provided that the examined CT has been preliminarily identified. A simple scalar model for the CTs magnetic core, taking into account saturation as well as hysteresis and eddy currents phenomena, has been implemented in a software compensation routine. This allows us to improve the accuracy in the reproduction of the primary current, in the case of both sinusoidal and distorted current waveforms (provided that DC components are not present). Many experimental tests, under different practical situations, have been performed. The results clearly show that the proposed technique is able to significantly reduce, in comparison with traditional methods, the errors introduced by current transformers